A huge undescribed diversity of the subgenus Hystricochaetonotus (Gastrotricha, Chaetonotidae, Chaetonotus) in Central Europe - Rataj Križanová, Františka; Vďačný, Peter (European Journal of Taxonomy, 2022)
The subgenus Hystricochaetonotus Schwank, 1990 is one of the most species-rich subgenera of Chaetonotus Ehrenberg, 1830. It has a worldwide distribution and encompasses 37 species predominantly living in the benthos and periphyton of limnetic habitats. We have discovered further nine new species in running and stagnant waters in Slovakia (Central Europe): Ch. (H.) arcanus sp. nov., Ch. (H.) avarus sp. nov., Ch. (H.) gulosus sp. nov., Ch. (H.) iratus sp. nov., Ch. (H.) luxus sp. nov., Ch. (H.) mirabilis sp. nov., Ch. (H.) optabilis sp. nov., Ch. (H.) slavicus sp. nov., and Ch. (H.) superbus sp. nov. Their morphology was studied using differential interference contrast microscopy and subsequent morphometric analyses were carried out. In addition, the primary and secondary structures of their 18S, ITS2, and 28S rRNA molecules as well as their barcoding mitochondrial gene encoding for cytochrome c oxidase (COI) were analyzed. Species boundaries were tested also using the compensatory base change analysis. The new species could be well separated both morphologically and molecularly. The present barcoding analyses revealed that the nuclear ITS2 sequences represent a powerful DNA barcode in addition to the mitochondrial COI gene. According to the multi-gene phylogenetic analyses, the lineage leading to the last common ancestor of the ‘Hystricochaetonotus’ clade is the longest internal branch within the family Chaetonotidae Gosse, 1864. Since members of the subgenus Hystricochaetonotus are morphologically highly heterogeneous, parallel evolution of Chaetonotus-like and/or Hystricochaetonotus-like characters of scales and spines occurred during its radiation.